Strategies involving low-molecular-weight heparin for the treatment and prevention of venous thromboembolism in patients with obesity: A systematic review and meta-analysis - Liu, Junjie; Qiao, Xi; Wu, Mingdong; Wang, Haiyang; Luo, Hailong; Zhang, Haolong; Chen, Yikuan; Sun, Jianming; Tang, Bo (Frontiers in Endocrinology, 2023)
Introduction: Recent studies have indicated that the dosage of LMWH in patients with specific weights may be controversial. Therefore, we conducted a meta-analysis to explore an appropriate dosage of LMWH for the prevention and treatment of venous thromboembolism (VTE) in patients with obesity. Materials and methods: We searched the PubMed, EMBASE, and Cochrane Library databases up to July 23, 2022. Study selection, bias analysis, and information extraction were performed by three independent reviewers. The occurrence or recurrence of VTE and bleeding events were the primary outcomes we assessed. Results: Eleven studies (a total of 6266 patients) were included in the prevention group, and 6 studies (a total of 3225 patients) were included in the treatment group. For VTE prophylaxis, compared with the standard-dosage group, the high-dosage group had a lower incidence of VTE (OR: 0.47, 95% CI: 0.27-0.82, P=0.007) and a similar incidence of bleeding events (OR: 0.86, 95% CI: 0.69-1.08, P=0.020). For VTE therapy, compared to the standard-dosage group, the reduced-dosage group had a similar incidence of VTE recurrence (OR: 0.86, 95% CI: 0.11-6.84, P=0.89) but a lower incidence of bleeding events (OR: 0.30, 95% CI: 0.10-0.89, P=0.03). Conclusion: In patients with obesity, increasing the dosage of LMWH is a more appropriate option for the prevention of VTE. Due to the limited evidence, reducing the therapeutic dosage of LMWH requires careful consideration. Larger-scale, well-designed randomized controlled trials are necessary.